Domain-specific physical activity and sedentary behavior in relation to chronic kidney disease: a cross-sectional analysis of 24,950 U.S. adults in NHANES 1999–2012 - Nanhui Zhang; Jia Shi (Renal Failure)
The independent and domain-specific associations between physical activity (PA) and chronic kidney disease (CKD) remain underexplored. This study investigates the relationships between leisure-time, occupational, and transportation-related PA, along with sedentary behavior, and CKD prevalence in a nationally representative U.S. adult cohort. We analyzed 24,950 participants from the National Health and Nutrition Examination Survey (NHANES) 1999–2012. PA and sedentary behavior were assessed via validated questionnaires. Participants were classified based on adherence to physical activity guidelines (≥150 min/week). Multivariable logistic regression and restricted cubic splines were used to evaluate dose-response and non-linear associations. We found that meeting PA guidelines for total, leisure-time, and occupational PA was independently associated with lower odds of CKD (OR [95% CI]: 0.82 [0.73–0.93], 0.86 [0.76–0.97], and 0.85 [0.76–0.96], respectively). No significant association was observed for transportation-related PA. Sedentary behavior exceeding 6 h/day was associated with higher CKD prevalence. These associations were more pronounced in women, and dose-response patterns were evident across PA domains. This large-scale cross-sectional study identifies robust, domain-specific inverse associations between PA and CKD prevalence, particularly among women. Findings support stratified behavioral interventions targeting leisure and occupational activity domains, alongside sedentary behavior reduction, to mitigate CKD burden. Prospective studies are warranted to confirm causal pathways.